Sustainable road bases with microbial carbonate precipitation - Porter, H.; Dhami, Navdeep; Mukherjee, Abhijit (2016)
© 2016 International Committee of the SCMT conferences. All rights reserved. The Australian road network is nearly a million kilometres long of which 83% can be classified as rural roads. The size and remote nature of Australia’s road network poses unique challenges in terms of monitoring their condition as well as maintenance costs. Cement stabilisation is a practice commonly used in Australian road bases to improve their durability and avoid cost of inspection and repair. Due to the sheer length of the road network a huge quantity of cement is consumed in stabilisation work making the practice unsustainable. This paper explores a sustainable alternative through augmentation of traditional cement based stabilisation with microbial carbonate precipitation in Australian road base materials. Carbonate producing ureolytic strains of bacteria were isolated from Western Australian soil. Sand samples with a cement dosage of 7% have been subjected to microbial precipitation. The calcium carbonate crystals formed within the samples have been investigated by scanning electron microscopy and X-ray diffraction. Unconfined compressive strength (UCS) testing has been reported. Digital image correlation (DIC) technique has been utilised during UCS testing to extract more refined information such as local deformation and strain build up. The results show that microbial precipitation is able to significantly increase the strength of a cement stabilised material and can considerably improve the technological, economic and social sustainability of Australian road bases. A serendipitous spin off of this research is the discovery of the ability of DIC to predict the regions of failure of road base material at very early stages. DIC may provide a very useful tool for road asset management.